Development of Digital Marketing Applications for Jombang Tourism and Culture Based on Android (User) - Aminah, Siti; Sufaidah, Siti (LPPM Universitas KH. A. Wahab Hasbullah, 2024)
ABSTRACT The development of global tourism is very rapid, including in Indonesia, especially in the city of Jombang. Jombang is known to have interesting cultural and natural tourism objects. Digital marketing describes the use of digital technology to support marketing functions. This research aims to study the use and development of digital marketing in the promotion of tourism and culture in Jombang. The digital marketing application developed is designed to help users find information about the natural beauty, tourist attractions, and cultural richness of Jombang. In addition, this application facilitates the search and discovery of included tourist sites, which is expected to have a positive impact on the development of tourism and cultural preservation in Jombang. This Android-based digital marketing application has several main features: Main Page (Home): Displays a summary or recommendation of tourist attractions in Jombang. Popular Tourism List: Presents the most visited tourist attractions. Maps: Helps users find routes to tourist sites. Tourist Description: Provides detailed information about a particular tourist destination. Popular Culture List: Displays cultural activities or events that are often held in Jombang. Tourist Type and Sub-district Filters: Allows users to select the type of tourism and sub-district of interest. Keywords : Development, Digital Marketing, Android, Tourism, Culture.